MASS BALANCE APPROACH AT PALM CARBON CYCLE - Abdul Kahar (Universitas Lambung Mangkurat, 2022)
Development of Indonesian palm oil industry, not only contributes positively to economic sector. Biggest challenge lies in the negative issues of oil palm development, namely environmental issues. Land use change, forest clearing, deforestation, peat land for palm plantation expansion are environmental issues because they are considered to disturb the balance of greenhouse gases. The use of non-standard fertilizers and POME processing can also increase CO2 emissions, which in turn will reduce carbon storage in vegetation and soil. Soil is the most potent organic carbon sink compared to plants. Soil is an organic carbon pool (reservoir) that accumulates organic carbon in and organic carbon out. The accumulated carbon is influenced by aboveground biomass, belowground biomass, necromass, litter and soil organic matter. So that the development of oil palm is accused of being one of the factors that play a role in soil organic carbon (SOC), soil carbon loss (SCL), net carbon balance (NCB), or greenhouse gasses (GHG) emissions. Where this is a very important component in the palm carbon cycle that has an impact on the global climate. The mass balance approach to the palm carbon cycle obeys the law of conservation of mass. The mass of palm carbon before and after processing is constant. This means that the total mass of palm carbon during the process does not change, only a phase change occurs, namely solid, liquid, and gas.